Epidemiologia da hipertensão arterial em uma população urbana de baixa renda - Feijão, Adelina Maria Melo (2000)
The High Blood Pressure has been considered to be one of the most important pathologies for the Public Health, due to its importance for the occurrence of the cardiovascular diseases, specially the heart attack, the vascular cerebral disease and the congestive cardiac insufficiency. Many risk factors related to the High Blood Pressure have been described in the literature. However, in our State, relative importance of each one of them is still little known. The aim of the present study was to verify the prevalence and the relative importance of some classic risk factor for the High Blood Pressure in an adult population with low income, as well as to measure the association between domestic work and High Blood Pressure in women. The study area was “The Conjunto Habitacional Metropolitano”, a group of apartment blocks for low income people in the Municipality of Caucaia, Ceará State, Brazil. A survey was carried out, in house by house basis, in 760 households in a continuos area of the “Conjunto Habitacional Metropolitano”. A total of 1,248 individuals of both sexes and thirty years old or older was enrolled in this survey. During the survey an interview was carried out, a anthopometric exam was conducted and the blood pressure of all individuals was measured. It was observed a prevalence of arterial blood pressure of 23,96% (VI JNC) and 9,85% (WHO). The prevalence of overweight was 35,76% and the obesity was of 15,18%. Women presented an significant increase on the prevalence of overweight and obesity as the age goes on. On the other hand, men did not show this increase. Among the individuals with overweigth and obesity, the prevalence of high blood pressure (VI JNC) was 25,42% in women and 40,11% in men. it was not observed any significant difference of high blood pressure between the sexes. A higher society level and a longer school live were associated with a smaller prevalence of arterial high blood pressure. To measure the association between the work done at home and high blood pressure in women, was executed a case-control study. It involved 147 cases and 300 controls. The average of age was of 30 to 55 years old. The cases were women whose PAD was equal or higher than 90 mm Hg and/or PAS was equal or higher than 140 mm Hg. The controls were women with PAD lower than 80 mm Hg and PAS lower than 120 mm Hg. The domestic work was measured in hours during the day. The activities studied were: wash, cook, clean, and care with children, oldies and people with disease. Form the total, 99,0% (442), did home work and 1% (5) said that they had no work at home, 9,50% (42) worked outside but still doing domestic work, 12,44% (55) do not practice domestic work at home. and 13,57% (60) do not practice domestic work outside (sellers, secretaries). It was verified a significant association between doing domestic work out of the house and High Blood Pressure (OR=2,17; CI 95%: 1,04 – 4,53) adjusted for the following variables: age, IMC, income and hours of domestic work at home. This variables have also shown to be significantly associated with High Blood Pressure. The other kinds of occupation did not show any significant association with High Blood Pressure, even domestic work at home. This findings point out to the importance of the obesity in the overall adult population, while a possible factor of intervention, as well as the need of prospective studies specifically to verify the association between occupation and High Blood Pressure in women.